Neuron-radial glial cell communication via BMP/Id1 signaling is key to long-term maintenance of the regenerative capacity of the adult zebrafish telencephalon - Zhang, Gaoqun; Lübke, Luisa; Chen, Fushun; Beil, Tanja; Takamiya, Masanari; Diotel, Nicolas; Strähle, Uwe; Rastegar, Sepand (Cells, 2021)
The central nervous system of adult zebrafish displays an extraordinary neurogenic and regenerative capacity. In the zebrafish adult brain, this regenerative capacity relies on neural stem cells (NSCs) and the careful management of the NSC pool. However, the mechanisms controlling NSC pool maintenance are not yet fully understood. Recently, Bone Morphogenetic Proteins (BMPs) and their downstream effector Id1 (Inhibitor of differentiation 1) were suggested to act as key players in NSC maintenance under constitutive and regenerative conditions. Here, we further investigated the role of BMP/Id1 signaling in these processes, using different genetic and pharmacological approaches. Our data show that BMPs are mainly expressed by neurons in the adult telencephalon, while id1 is expressed in NSCs, suggesting a neuron-NSC communication via the BMP/Id1 signaling axis. Furthermore, manipulation of BMP signaling by conditionally inducing or repressing BMP signaling via heat-shock, lead to an increase or a decrease of id1 expression in the NSCs, respectively. Induction of id1 was followed by an increase in the number of quiescent NSCs, while knocking down id1 expression caused an increase in NSC proliferation. In agreement, genetic ablation of id1 function lead to increased proliferation of NSCs, followed by depletion of the stem cell pool with concomitant failure to heal injuries in repeatedly injured mutant telencephala. Moreover, pharmacological inhibition of BMP and Notch signaling suggests that the two signaling systems cooperate and converge onto the transcriptional regulator her4.1. Interestingly, brain injury lead to a depletion of NSCs in animals lacking BMP/Id1 signaling despite an intact Notch pathway. Taken together, our data demonstrate how neurons feedback on NSC proliferation and that BMP1/Id1 signaling acts as a safeguard of the NSC pool under regenerative conditions.
Gesehen am 07.12.2021